PEMASARAN DESTINASI BRANDING MELALUI AKTIVITAS BRAND ACTIVATION ( Study Palembang TTI Expo 2017) - Prihantono, Dwi Nurul (Aksara Public, 2018)
The tourism industry is an industry that is relied upon and developed as one of the sectors driving economic growth, because the tourism sector significantly affect the economy of people in the region. To develop the potential of tourism in the region in need of a branding destination that aims to market the potential of an area. One of the most effective activities in strengthening branding is through brand activation activity. Brand activation is an activity that contributes to build trust between consumers, society and products. This research tries to trace the importance of branding destination through brand activation activity. This research uses qualitative paradigm with descriptive method. Data were obtained through direct and indirect interviews, Focus Group Discussion, literature review, and documentation.